Financial Management Practices and Growth of Small and Medium Enterprises: A Case Study of Mukono Town ,Upper Kawuga - Elizabeth Kongai (Uganda Christian University, 2023)
The study will examine the aspect of the financial management practices and growth of small and medium enterprises in Mukono Town, Upper Kawuga. The objective of the study is to determine the effects of capital budgeting techniques on the financial performance of small and medium enterprises, to determine the effects of budgetary controls on the financial performance of small and medium enterprises and to determine the effects of record keeping on the financial performance of small and medium enterprises. The study used a descriptive research design with a population of 120 SMEs and a sample of 100 was drawn from retail shops, wholesale Trading Super Markets, Cottage Industry and a questionnaire was employed in the collection of data. However, the study aims at finding out whether financial management practices has impact on the Growth of small and medium enterprises a case study Mukono town, Upper Kawuga . The findings will show whether there is a positive effect of capital budgeting techniques on the growth.
This is a dissertation.